Wozu erinnern wir uns? Einige Fragen an die Geschichtswissenschaften - Harald Welzer (Österreichische Zeitschrift für Geschichtswissenschaften, 2005)
Based on results of neurobiological and psychological research the paper gives some suggestions on what memory, history, and truth are. Episodic and autobiographic memory systems are human-specific and enabled human phylogeny to move out of the slow evolutionary process establishing a co-evolutionary sphere. Evolutionary developmental pace is accelerated by social means as communication, symbolisation and tradition. The co-evolutionary developmental environment of humans is history. History normally deals with questions of historical truth, provided by diverse sources and methodological standards. But truth is a function of social agreement and is necessarily connected with emotional value. How can historical science deal with these fundamental non-objective qualities of truth epistemologically and theoretically?